Dynamic roles of small RNAs and DNA methylation associated with heterosis in allotetraploid cotton (Gossypium hirsutum L.) - Rasmieh Hamid; Feba Jacob; Zahra Ghorbanzadeh; Leila Jafari; Omran Alishah (BMC Plant Biology, 2023)
Abstract Background Heterosis is a complex phenomenon wherein the hybrids outperform their parents. Understanding the underlying molecular mechanism by which hybridization leads to higher yields in allopolyploid cotton is critical for effective breeding programs. Here, we integrated DNA methylation, transcriptomes, and small RNA profiles to comprehend the genetic and molecular basis of heterosis in allopolyploid cotton at three developmental stages. Results Transcriptome analysis revealed that numerous DEGs responsive to phytohormones (auxin and salicylic acid) were drastically altered in F1 hybrid compared to the parental lines. DEGs involved in energy metabolism and plant growth were upregulated, whereas DEGs related to basal defense were downregulated. Differences in homoeologous gene expression in F1 hybrid were greatly reduced after hybridization, suggesting that higher levels of parental expression have a vital role in heterosis. Small RNAome and methylome studies showed that the degree of DNA methylation in hybrid is higher when compared to the parents. A substantial number of allele-specific expression genes were found to be strongly regulated by CG allele-specific methylation levels. The hybrid exhibited higher 24-nt-small RNA (siRNA) expression levels than the parents. The regions in the genome with increased levels of 24-nt-siRNA were chiefly related to genes and their flanking regulatory regions, demonstrating a possible effect of these molecules on gene expression. The transposable elements correlated with siRNA clusters in the F1 hybrid had higher methylation levels but lower expression levels, which suggest that these non-additively expressed siRNA clusters, reduced the activity of transposable elements through DNA methylation in the hybrid. Conclusions These multi-omics data provide insights into how changes in epigenetic mechanisms and gene expression patterns can lead to heterosis in allopolyploid cotton. This makes heterosis a viable tool in cotton breeding.